A call for critical dialogue: EAP assessment from the Practitioner's perspective in Canada. Issue 35 (September 2018) - Huang, Li-Shih
Abstract: Using an explanatory sequential design, this study integrated survey and interview data gathered from 35 English-for-academic-purposes (EAP) practitioners across 14 institutions in Canada in order to address questions associated with their assessment practices. Specifically, we explored the participants' training, experience, and perceived skills in testing and assessment; their perceptions about EAP testing and assessment; their approaches to and practices of EAP testing and assessment; and their testing- and assessment-related professional development needs. In addition to revealing the participating EAP instructors' assessment approaches and practices in the Canadian context, the results highlighted a reported paucity of training in EAP testing and assessment both within and outside of teacher-education programs. They also revealed self-perceived gaps of EAP instructors regarding their lack of assessment knowledge, skills in developing tests, skills in aligning needs with tests and assessments, and self-confidence in designing, modifying, and implementing tests. The sharing of these results is intended to raise awareness of the current testing and assessment practices of EAP instructors in the Canadian context, with the hope of opening a dialogue about them as well as reflecting on ways to encourage the sharing of knowledge, skills, and understanding about these practices within the professional community.